Antioxidant and Rutin Content Analysis of Leaves of the Common Buckwheat (Fagopyrum esculentum Moench) Grown in the United Kingdom: A Case Study - Solomon Habtemariam (MDPI AG, 2019)
The common buckwheat, Fagopyrum esculentum Moench (Polygonaceae) is a gluten-free pseudocereal that has been gaining in popularity in recent years as a low-calorie and nutrient-rich healthy food option. Buckwheat farming is common in Eastern European countries and the Far East, while in the UK and other Western European countries, the plant has limited medicinal or food applications. The vegetative parts, particularly the leaves and flowers, are among the best-known sources of the bioactive compound, rutin. Hence, functional foods originated from buckwheat leaves are common, although the scope of such applications is limited by phototoxicity associated with the fagopyrin composition. Here, the antioxidant and rutin composition of the leaves of the plant grown in the UK are assessed. The methanol extract of the leaves displayed a potent DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging effect along with reducing power. Quantitative High Performance Liquid Chromatography (HPLC)-based analysis showed the rutin content of the leaves as 3417 mg/100g (on dry weight (DW) basis). The identity of rutin was also confirmed by isolation and structural elucidation based on spectroscopic studies. From the chemical content analysis, including fagopyrin levels and the antioxidant assays, UK-grown buckwheat has potential as a commercial source of rutin or as a functional food.